2011
DOI: 10.1177/1029864911423146
|View full text |Cite
|
Sign up to set email alerts
|

Musically puzzling II: Sensitivity to overall structure in a Haydn E-minor sonata

Abstract: Previous studies have suggested that listeners are insensitive to the overall tonal structure of musical pieces. In Part I of this report (Granot & Jacoby, 2011) we reexamined this question by means of a puzzle task using 10 segments of Mozart's B flat major piano sonata K. 570/I. As expected, subjects had difficulty in recreating the original piece. However, their answers revealed some interesting patterns, including (1) Some sensitivity to the overall structure of A-B-A' around the non-stable B section; (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Of the participants, these include: moderate or high degree of music, education and training, some or extensive training in music, absolute, partial absolute, or relative listener. Three studies gave separate split points: one study indicated an intermediate musician to have at least five years of private instrumental lessons, and an expert musician to have a minimum of 10 years of private instrumental lessons (Bishop, Bailes, & Dean, 2013); two studies indicated a trained musician to have a minimum of seven years of formal music training, and a highly trained musician to have over nine years of formal music training (Granot & Jacoby, 2011, 2012). e “Musical practitioner,” “high experience” and “intonation sensitive” participants. f Standard deviation shown in parentheses. g First and third quartile shown in parentheses. h Statistics shown are for those studies that reported a split point for MEC (n indicated in Split Point Yes column).…”
Section: Resultsmentioning
confidence: 99%
“…Of the participants, these include: moderate or high degree of music, education and training, some or extensive training in music, absolute, partial absolute, or relative listener. Three studies gave separate split points: one study indicated an intermediate musician to have at least five years of private instrumental lessons, and an expert musician to have a minimum of 10 years of private instrumental lessons (Bishop, Bailes, & Dean, 2013); two studies indicated a trained musician to have a minimum of seven years of formal music training, and a highly trained musician to have over nine years of formal music training (Granot & Jacoby, 2011, 2012). e “Musical practitioner,” “high experience” and “intonation sensitive” participants. f Standard deviation shown in parentheses. g First and third quartile shown in parentheses. h Statistics shown are for those studies that reported a split point for MEC (n indicated in Split Point Yes column).…”
Section: Resultsmentioning
confidence: 99%
“…By restating phrases and other structures that have already occurred, often multiple times, the creators of music (composers, improvisers) signal to listeners that such structures are significant, and worthy of revisiting for deeper reflection. The consequence of this repetition is that even listeners without formal training are highly sensitive to basic aspects of conventionalized structure, such as sonata form in a classical work or verse-chorus form in pop music (Granot & Jacoby, 2011; Neuhaus, 2013; Vallières et al, 2009).…”
Section: Toward a Music Appreciation Frameworkmentioning
confidence: 99%
“…Due to its complexity as a musical phenomenon and the general tendency of surface features to attract listeners’ attention, harmony is often taught and studied using as simple realizations as possible (e.g., block chords in middle register, same timbre, same duration; see, for example, Christensen, 2006; Snodgrass, 2016). Investigating the complex connection between harmony and other musical features is difficult when real pieces of music are used (Deliège et al, 1996; Granot & Jacoby, 2011, 2012; Williams, 2005). Simpler stimuli, such as block chords, instantiate harmony in a relatively clear way by reducing the complexity of some surface features such as the rhythm and texture while still allowing sufficient freedom and control for the manipulation of other musical features, such as chord voicings, voice leading between chords, and melodic line formed of the highest pitch of each chord.…”
Section: Chord Types and Voicingsmentioning
confidence: 99%